2017
DOI: 10.1038/srep44432
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion inhibition of mild steel in 1M HCl by D-glucose derivatives of dihydropyrido [2,3-d:6,5-d′] dipyrimidine-2, 4, 6, 8(1H,3H, 5H,7H)-tetraone

Abstract: D-glucose derivatives of dihydropyrido-[2,3-d:6,5-d′]-dipyrimidine-2, 4, 6, 8(1H,3H, 5H,7H)-tetraone (GPHs) have been synthesized and investigated as corrosion inhibitors for mild steel in 1M HCl solution using gravimetric, electrochemical, surface, quantum chemical calculations and Monte Carlo simulations methods. The order of inhibition efficiencies is GPH-3 > GPH-2 > GPH-1. The results further showed that the inhibitor molecules with electron releasing (-OH, -OCH3) substituents exhibit higher efficiency tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(71 citation statements)
references
References 73 publications
(125 reference statements)
3
66
1
1
Order By: Relevance
“…Optimized structure, HOMO and LUMO for studied inhibitor molecules in aqueous medium is shown in Figure . The investigated molecules SS1 & SS2 differ from one another by the presence of hetero atoms, which change the properties of molecules . Table shows calculated electronic properties like I , A , Δ E , μ, Χ , η and Δ N of SS1 & SS2 in gas phase and aqueous medium .…”
Section: Resultscontrasting
confidence: 66%
“…Optimized structure, HOMO and LUMO for studied inhibitor molecules in aqueous medium is shown in Figure . The investigated molecules SS1 & SS2 differ from one another by the presence of hetero atoms, which change the properties of molecules . Table shows calculated electronic properties like I , A , Δ E , μ, Χ , η and Δ N of SS1 & SS2 in gas phase and aqueous medium .…”
Section: Resultscontrasting
confidence: 66%
“…The heteroatoms play a significant role in the adsorption process of inhibitor molecules onto the mild steel surface (Figure 12). Due to the unshared pair of electrons, the heteroatoms N, O, S, and P containing inhibitor molecules can easily be protonated in strong corrosive electrolyte (HCl, H 2 SO 4 , HNO 3 , and H 3 PO 4 ) solution [26,27]. Therefore, the corrosion inhibitors studied in this paper exist as protonated species in 1 M HCl solution [60].…”
Section: Mechanism Of Inhibitionmentioning
confidence: 95%
“…Methionine, methionine sulfoxide, and methionine sulfone at a respective concentrations of 149, 165, and 181 ppm in 1 M HNO 3 at 30 • C have been shown to attain an inhibition efficiency of 79, 85, and 88%, respectively [25]. A literature surveys showed that there are numerous research articles that dealt with N, O, S, or P-containing compounds for metallic corrosion inhibition [26][27][28], but so far, no report is available that deals with all four heteroatoms (N, O, S, and P) in a single polymer, based on residual methionine, for effective metallic corrosion inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion inhibitors find application in minimizing metallic waste in engineering materials, in addition to the advantages of versatility and cost effectiveness when compared to other corrosion protection methods [10,13]. Most of the effective inhibitors are either from biomass precursors or chemical compounds containing hetero-atoms such as oxygen, nitrogen, and sulfur with multiple bonds in their molecules through which they are adsorbed on the metal surface [14][15][16]. This adsorption depends on certain physiochemical properties of the inhibitors: functional group, electron density at the donor atom, n-orbital character, and the electron structure of the molecule.…”
Section: F E + H + → F E 2+ + Hmentioning
confidence: 99%